Attenuating Ischemia-Reperfusion Injury in Kidney Transplantation by Perfusing Donor Organs With siRNA Cocktail Solution. Issue 4 (April 2016) - Zheng, Xiufen; Zang, GuoYao; Jiang, Jifu; He, Wenqing; Johnston, Nathan J.; Ling, Hong; Chen, Ruiqi; Zhang, Xusheng; Liu, Yanling; Haig, Aaron; Luke, Patrick; Jevnikar, Anthony M.; et al.
Abstract : Background: Ischemia-reperfusion (I/R) injury is the major cause of delayed renal graft function in kidney transplantation. To date, there are no effective therapeutic approaches for preventing I/R injury. We previously reported that treatment of animals with small interference RNA (siRNA) would prevent warm I/R injury in nontransplant models and cold I/R injury in heart transplantation. In the present study, we further explore the feasibility of protecting grafts from extended cold I/R injury as applied to kidney transplantation by downregulating I/R-associated genes using siRNA. Methods: Donor kidneys were intra-arterially perfused with siRNA containing solution during donor excision and preserved in siRNA containing solution. The siRNA-treated donor organs were then implanted into syngeneic recipient mice, and the 2 original kidneys were removed from the recipient. The effect of siRNA solution on extended cold I/R injury was determined by assessing renal function, histopathological change, cell apoptosis, and inflammation. Results: The perfused siRNA solution knocked down the expression of complement 3, RelB, and Fas in the kidney at the mRNA and protein levels. Administration of siRNA solution reduced the levels of blood urea nitrogen and serum creatinine as compared with control groups. The siRNA cocktail decreased cell apoptosis and histopathological changes in the kidney and prolonged graft survival. The siRNA cocktail also reduced the expression of proinflammatory cytokines, IL-6, and TNFα. Conclusions: In conclusion, this is the first demonstration that perfusing donor organs with an siRNA cocktail solution can induce gene silencing in the kidney and prevent kidneys from extended cold I/R injury in kidney transplantation, highlighting the promise of the clinical application of siRNA-based therapies in the preservation of donor organs. Abstract : The authors report that the intra-arterial perfusion of siRNA to knock down the expression of C3, RelB and Fas in donor kidneys protected them from extended cold ischemia reperfusion injury and prolonged their survival in mice posttransplant. Supplemental digital content is available in the text.